Decay of Perturbations in a Quantum-Dot-Optical Microcavity Model - González, A. (Revista Cubana de Física, 2014)
The dynamics of small perturbations against the stationary density matrix of a pumped polariton system with only one photon polarization is studied. Depending on the way the system is pumped and probed, decay times ranging from 30 to 5000 ps are found. The large decay times under resonant pumping are related to a bottleneck effect in the decay of the excess (probe) populations of dark polariton states. No singular behaviour at the threshold for polariton lasing is observed.